(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
ABSTRACT While it has been well documented in the previous studies that upwelling events in the southern Makassar Strait (MAK) during the Southeast Monsoon (SEM) period are associated with low sea surface temperature (SST) and high chlorophyll-a (Chl-a) concentrations in the seawater, the dynamic and physical processes that trigger these upwelling events are still less well understood. In the present study we proposed a mechanism of the upwelling event using a numerical model of the Regional Ocean Modeling System (ROMS). Model validations showed a high correlation of SST climatology between the model and the NOAA-AVHRR satellite data. Moreover, velocity fields of the Indonesian Throughflow (ITF) Makassar in Libani Channel was well reproduced by proposed model, revealing an intensification of the flow centered near 120 m depth, which is in good agreement with the observation data. The model demonstrated that during the SEM period strong southeasterly winds that blow over southern Sulawesi Island can increase high vertical diffusivity and heat loss through heat flux. Hence, these physical processes lead to increased vertical mixing that, in turn, generates low SST, as a proxy of upwelling event. Furthermore, the upwelling process is enhanced by the ITF Makassar jet that creates large circular eddies flow due to complex topographic within the triangle area of southern Makassar - eastern Java Sea - western Flores Sea. The eddies generate the area of convergence offshore along the ITF pathways and divergence area in the coastal waters close to southern Sulawesi Island. Model experiment with closing/opening Selayar Strait revealed a change of intensity and area of upwelling, suggesting that the Selayar Island forms a barrier for the outflow from MAK to northern part of Flores Sea. Keywords: Upwelling, ITF Makassar, SE monsoon winds, ROMS-AGRIF, Makassar Strait.